Human health risks arising from nitrate in potatoes consumed in Iran and calculation nitrate critical value using risk assessment study. Issue 3 (2nd April 2016) - Yeganeh, Mojgan; Bazargan, Kambiz
ABSTRACT: Because of the low amount of nitrogen and organic matter in most soils of Iran, it is recommended to use nitrogen fertilizers in potato fields. Nitrate accumulates in plants naturally and if it enters into the human body it can threaten human health. There is not enough information about nitrate distribution in potatoes in Iran and a scientific value of critical level of nitrate in potatoes in Iran. The objective of this study, then, is to: determine the amount of nitrate in potatoes produced in different parts of Iran, assess the human health risks arising from potatoes nitrate, and calculate the critical concentration of nitrate in potato, using a risk assessment study and Iranian food basket. Two hundred and seventy-seven samples were collected from main provinces producing potatoes in Iran. Concentration of nitrate was measured in all samples. Results showed that Kerman province has more nitrate pollution and non cancer risk arising from nitrate. The most sensitive group to nitrate was boys 7–14 years old residing in Kerman province. Critical value of nitrate in potato for this receptor group, then for Iranian society in conservative conditions, was calculated using intake equations introduced by the USEPA and considering Iranian food basket as 246 mg kg –1 .